Patients suffering from non-IgE-mediated cow's milk protein intolerance cannot be diagnosed based on IgG subclass or IgA responses to milk allergens - Hochwallner, H.; Schulmeister, U.; Swoboda, I.; Twaroch, T. E.; Vogelsang, H.; Kazemi-Shirazi, L.; Kundi, M.; Balic, N.; Quirce, S.; Rumpold, H.; Fröschl, R.; Horak, F.; et al. (Allergy, 2011)
{Cow's milk is one of the most common causes of food allergy. In two-thirds of patients, adverse symptoms following milk ingestion are caused by IgE-mediated allergic reactions, whereas for one-third, the mechanisms are unknown. Aim of this study was to investigate whether patients suffering from non-IgE-mediated cow's milk protein intolerance can be distinguished from persons without cow's milk protein intolerance based on serological measurement of IgG and IgA specific for purified cow's milk antigens.|We determined IgG(1-4) subclass and IgA antibody levels to purified recombinant αS1-casein, αS2-casein, β-casein, κ-casein, α-lactalbumin, and β-lactoglobulin in four patient groups by ELISA: Patients with IgE-mediated cow's milk allergy (CMA
Keywords: Adolescent Adult Aged Allergens Animals Child Child; Preschool Complement System Proteins Epitopes Female Humans Immunoglobulin A Immunoglobulin E Immunoglobulin G Infant Male Middle Aged Milk Hypersensitivity Milk Proteins Protein Binding Young Adult